The impact of thermal treatment on comminution performance of blue mussel (Mytilus edulis) and South African abalone (Haliotis midae) shell waste - Lesofe, Ts’olo Ernest (Stellenbosch : Stellenbosch University, 2025)
Thesis (MEng)--Stellenbosch University, 2024.